Elementary School Teachers’ Readiness in Integrating STEM into Science Learning - Awalina Barokah; Wiyanto Wiyanto (Proceedings of International Conference on Science, Education, and Technology, 2026)
The integration of Science, Technology, Engineering, and Mathematics (STEM) into elementary science learning has gained increasing recognition as a promising approach for developing students' twenty-first-century competencies. However, successful STEM implementation depends largely on teachers' readiness to integrate interdisciplinary learning into classroom practices. This study aimed to examine the level of readiness among elementary school teachers in integrating STEM into science learning. A quantitative descriptive survey design was employed, involving 59 elementary school teachers. Data were collected using a validated questionnaire consisting of four dimensions: STEM knowledge, technological readiness, pedagogical readiness, and STEM implementation readiness. Data were analyzed using descriptive statistics, including mean scores and standard deviations. The findings revealed that teachers demonstrated a high level of readiness across all dimensions, with an overall mean score of 3.85. Technological readiness obtained the highest mean score (M = 3.98), followed by STEM knowledge (M = 3.86), while pedagogical readiness and STEM implementation readiness shared the lowest mean score (M = 3.79). Teachers showed strong interest in participating in STEM-related professional development and expressed readiness to implement STEM in science classrooms. Nevertheless, limited hands-on STEM experience and difficulties in designing STEM-based learning activities and assessments remain notable challenges. The findings indicate that while elementary school teachers possess positive perceptions and substantial readiness toward STEM integration, continuous professional development and institutional support are necessary to strengthen pedagogical competencies and practical implementation. These findings offer empirical evidence to inform teacher training program development and policy-making aimed at advancing STEM education at the elementary level.